Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Kantor Kecamatan Ciputat - Apriliana, Rina; Prasetyo, Hendri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The purpose of this study was to determine the effect of motivation and work discipline on employee performance. both partially and simultaneously. The method used in this study is a quantitative method. The sampling technique used is saturated sampling, which uses a sample of 43 respondents. The data analysis technique used is statistical analysis with validity test, reliability test, classical assumption test, simple linear test, multiple linear regression test, coefficient of determination, hypothesis t test and hypothesis f test. The results of the study of motivation and work discipline on employee performance